ANALYSIS OF MSME READINESS IN ADOPTING SHARIA FINANCIAL TECHNOLOGY: A Study In Malang City - Yasin Nur Rohim; Dharmawan Iqbal Akbar; Fathimatus Zahro Fazda Oktavia; Rosy Aprieza Puspita Zandra (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2026)
This study examines the readiness of Micro, Small, and Medium Enterprises (MSMEs) in Malang City to adopt Sharia-based financial technology (Sharia fintech). The research method used is a qualitative descriptive approach through direct observation, semi-structured interviews, and documentation to explore factors influencing MSME readiness. The results show that despite supporting digital infrastructure, low Sharia financial literacy and limited human resources are major obstacles. Support from the government and Sharia financial institutions, as well as intensive training, are needed for MSMEs to optimally utilize Sharia fintech, increasing their competitiveness and business sustainability in the digital era. With increased Sharia financial literacy and strengthened digital infrastructure, it is hoped that MSMEs in Malang City can adapt more quickly and optimize the potential of Sharia fintech. This study also emphasizes the need for strong synergy between the government, Sharia financial institutions, and MSMEs to create a business ecosystem that supports Sharia-based financial sustainability and inclusion